Oligomeric state and structural stability of two hyperthermophilic beta-glucosidases from Thermotoga petrophila - Colussi, Francieli; Silva, Viviam M. da; Miller, Ian; Cota, Junio; Oliveira, Leandro Cristante de [UNESP]; Oliveira Neto, Mario de [UNESP]; Squina, Fabio Marcio; Garcia, Wanius (Springer, 2015)
The beta-glucosidases are enzymes essential for several industrial applications, especially in the field of plant structural polysaccharides conversion into bioenergy and bioproducts. In a recent study, we have provided a biochemical characterization of two hyperthermostable beta-glucosidases from Thermotoga petrophila belonging to the families GH1 (TpBGL1) and GH3 (TpBGL3). Here, as part of a continuing investigation, the oligomeric state, the net charge, and the structural stability, at acidic pH, of the TpBGL1 and TpBGL3 were characterized and compared. Enzymatic activity is directly related to the balance between protonation and conformational changes. Interestingly, our results indicated that there were no significant changes in the secondary, tertiary and quaternary structures of the beta-glucosidases at temperatures below 80 A degrees C. Furthermore, the results indicated that both the enzymes are stable homodimers in solution. Therefore, the observed changes in the enzymatic activities are due to variations in pH that modify protonation of the enzymes residues and the net charge, directly affecting the interactions with ligands. Finally, the results showed that the two beta-glucosidases displayed different pH dependence of thermostability at temperatures above 80 A degrees C. TpBGL1 showed higher stability at pH 6 than at pH 4, while TpBGL3 showed similar stability at both pH values. This study provides a useful comparison of the structural stability, at acidic pH, of two different hyperthermostable beta-glucosidases and how it correlates with the activity of the enzymes. The information described here can be useful for biotechnological applications in the biofuel and food industries.
Keywords: Beta-Glucosidase; Cellulose; Biomass; T. petrophila; Hyperthermostable; Biofuels